Paleogeomorphology reconstruction and its control on sand dispersal systems: a case study from the Pinghu formation in the Hangzhou slope belt, Xihu Sag, East China sea shelf basin - Qin, Lanzhi; Xu, Jie; Xu, Donghao; Liu, Hao; Cai, Kun (Frontiers in Earth Science, 2025)
Paleogeomorphology, as a key factor influencing depositional environments, plays a critical role in sedimentary processes and sediment distribution. Although considerable re-search has been conducted on paleogeomorphology and its control on sand bodies in the Xihu Sag, most studies have focused on reconstructing the overall geomorphic framework of the basin. However, limited attention has been given to the fine-scale reconstruction of intra-basin micro-geomorphology and its control on the types and distribution patterns of sedimentary sand bodies, especially the Hangzhou Slope area have received limited attention. This study applies the seismic virtual extrapolation method and mudstone sonic analysis to reconstruct the paleogeomorphology of the Pinghu Formation in the Hang-zhou Slope Belt of the Xihu Sag, aiming to elucidate the control of paleogeomorphic features on sedimentary sand body distribution. Based on detailed geological investigation and sedimentary analysis, combined with paleogeomorphic reconstruction techniques, geomorphic units and their spatial assemblages are identified, and the mechanisms by which variations in paleogeomorphic morphology and slope gradient influence sediment dispersal patterns are revealed. The reconstruction delineates the study area into four zones: steep uplifted areas, gently uplifted areas, slope-basin transitional zones, and basin areas. Integrated with sedimentary facies analysis, it is found that the gently uplifted areas are dominated by delta plain deposits, the slope-basin transitional zones dominated by delta front deposits, and the basin areas dominated by tidal sand ridges and shallow marine mudstones. Micro-geomorphic variations significantly affect sedimentary differentiation across zones. Areas with multiple types of slope breaks and moderate gradients tend to develop delta plain, delta front, and tidal sand ridge deposits; areas with fewer slope break types and gentler slopes favor delta plain and delta front deposition, with limited shelf sands in the delta front; while areas with steeper slopes and fewer slope breaks primarily develop delta plain and delta front deposits. This study enhances the understanding of the interaction between paleogeomorphology and sedimentation and provides new insights and approaches for paleoenvironmental reconstruction and hydrocarbon exploration.